Preliminary Investigation Into the Dynamic of Planing Hulls In Regular Waves Using the Smoothed Particle Hydrodynamics Method - Capasso, Salvatore; Tagliafierro, Bonaventura; Mancini, Simone; De Luca, Fabio; Martínez-Estévez, Iván; Domínguez, José Manuel; Altomare, Corrado; Crespo, Alejandro J. C.; Pensa, Claudio; Viccione, Giacomo (Volume 7: CFD & FSI, 2023)
In this work a numerical investigation on a planing hull in regular waves is carried out by means of the Smoothed Particle Hydrodynamics (SPH) meshfree method. The simulation of the interaction of such vessels with wave trains features several challenging characteristics, from the complex physical interaction, due to large dynamic responses, to the likewise heavy numerical effort. A novel numerical wave flume implemented within the SPH-based DualSPHysics open-source solver fulfills both demands, guaranteeing comparable accuracy with established proprietary CFD code without sharpening the computational load. The numerical wave flume uses ad-hoc open boundary conditions to reproduce the flow characteristics encountered by the hull during its motion, combining current and waves while adjusting their characteristics with respect to the vessel experimental towing speed. It follows a relatively small three-dimensional domain, where the potentiality of the SPH method in modeling free-surface flows interacting with moving structures is unleashed. This novel application of the SPH method shows its feasibility proving an overall good agreement with the experiments; it is established, hence, an interesting alternative procedure to simulate seakeeping test in several marine conditions with reasonable effort and accuracy.